Programação da produção em sistemas flowshop híbrido com buffers limitados - Lugo, Pedro Luis Miranda (2013)
This research studies the hybrid flowshop scheduling problem. In this production configuration, we have a set of jobs that has to be processed in a set of stages. At every stage we have a set of parallel machines available to process the jobs. All jobs have to be processed following the same production flow, from the first to the last stage. Every job has to be processed on one machine at each stage and each machine can process at most one job at a time. Some constraints commonly found in real production systems as unrelated parallel machines, limited buffers, sequence-dependent setup times (both anticipatory and non-anticipatory), machine eligibility, transportation times and release times for machines are also taken into account. The optimization criterion is the makespan, whose minimization is related to the efficient use of production resources. A mixed integer programming model is proposed and solved by the commercial solver CPLEX. The computational evaluation results indicate that the model is suitable just to solve instances up to nine jobs and five stages. Therefore, to solve larger instances (50-100 jobs), several heuristics and an iterated local search (ILS) algorithm are proposed and evaluated computationally. The results indicate that the ILS is able to obtain good quality solutions in short computation times.